Vehicle Detection System Using Ultrasonic And Magnetic Fields Sensors Based On LoRa Communication - Fakhri Afrizal; Bambang Nurcahyo Prastowo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2022)
Nowadays, privately owned vehicles still holds the position as the staple of transportation used by the majority of people, especially in Indonesia. Along with the increasing number of vehicles, its necessary to develop infrastructure that can support its usage. One of them is the development of a parking management system. The current conventional parking system in Indonesia requires users to surround the parking area to find an empty parking space. These activity takes time for the user so it is inefficient. To resolve that problem, it needs a smart parking system that can provide information about empty parking space location directly to the users.This study discusses the design of a vehicle detection system in the implementation of outdoor smart parking. The device that used in this research is the ultrasonic sensor HC-SR04 and the HMC5883L magnetic field sensor for the detection process and uses LoRa RFM95W to communicate with the gateway device. The smart parking system designed is able to detect the presence of car in the parking area and differentiate the car from other objects with a 100% success rate percentage.